2002
DOI: 10.1016/s0735-1097(02)01760-6
|View full text |Cite
|
Sign up to set email alerts
|

Action potential duration restitution kinetics in human atrial fibrillation

Abstract: Atrial fibrillation was related to steeply sloped (>1) APDR kinetics. The spatial dispersion of APDR in patients with chronic AF was greater than that of patients with paroxysmal AF and control subjects, indicating that the heterogeneity of APDR of the atrium plays an important role in the persistence of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 27 publications
14
91
0
Order By: Relevance
“…This hypothesis was inspired by several observations. First, elevated heart rates may lead to alternans of the T wave, 2 ventricular APD, 3 and, in preliminary reports from our laboratory and others, 4 atrial APD. Second, numeric simulations have elegantly described mechanisms through which rate-related APD alternans, indicating temporal heterogeneity in repolarization, may lead to reentry.…”
mentioning
confidence: 83%
“…This hypothesis was inspired by several observations. First, elevated heart rates may lead to alternans of the T wave, 2 ventricular APD, 3 and, in preliminary reports from our laboratory and others, 4 atrial APD. Second, numeric simulations have elegantly described mechanisms through which rate-related APD alternans, indicating temporal heterogeneity in repolarization, may lead to reentry.…”
mentioning
confidence: 83%
“…In some cases, more significant rate adaptation can be observed at the shortest CLs (Kim et al, 2002;Dobrev and Ravens, 2003). Similar alterations to those given by Courtemanche et al (1999) have been observed in other experiments as well (Dobrev and Ravens, 2003), including substantial reductions in I Ca,L (Bosch et al, 1999;Van Wagoner et al, 1999;Skasa et al, 2001;Workman et al, 2001) and I to (Van Wagoner et al, 1997;Bosch et al, 1999;Brandt et al, 2000;Grammer et al, 2000;Workman et al, 2001).…”
Section: Atrial Fibrillation-induced Changes In Rate Dependence and Mmentioning
confidence: 99%
“…The time course of restitution obtained by S 1 S 2 was fitted using a monoexponential equation and Origin 7.0 software (OriginLab Corp., Northampton, MA, USA), and the maximum slope of the APDR curve (slopemax) was obtained by the maximum value of the first derivative of the monoexponential equation fitting curve. [21][22][23][24] (Tables II and III). Electrophysiologic study: There was no significant difference between the groups in terms of the AH interval or the HV interval (Table IV).…”
Section: Construction Of the Action Potential Duration Restitution (Amentioning
confidence: 99%
“…Thus, we included male and female RA MAPD 80 in the control group. We did not compare the IACT and APD restitution characteristics between Brugada patients and control AF patients, but Kim, et al 22) compared the APD restitution curve between patients with chronic AF, paroxysmal AF, and control patients. Although the method of calculating slopemax was slightly different, they reported the slopemax was 1.4 ± 0.3 in chronic AF patients, 1.1 ± 0.4 in paroxysmal AF patients, and 0.5 ± 0.3 in control patients.…”
Section: Study Limitationsmentioning
confidence: 99%